Comparison of the Clinical Outcomes between Combined Femtosecond Laser-Assisted In Situ Keratomileusis and Corneal Cross Linking versus Combined Small-Incision Lenticule Extraction and Corneal Cross Linking - Yu Di; Fei Mo; Ying Li (Journal of Ophthalmology)
Purpose. The purpose of this study was to compare femtosecond laser-assisted in situ keratomileusis with prophylactic cross linking (FS-LASIK Xtra) and small-incision lenticule extraction with prophylactic cross linking (SMILE Xtra) in terms of their postoperative clinical outcomes. Methods. In this retrospective study, 24 patients (48 eyes) with myopia and myopia astigmatism were recruited from 2017 to 2018. All patients underwent comprehensive ophthalmic examinations preoperatively and follow-up visits at one and three months. Four patients (eight eyes) in each group were followed up for 12 months. The following were assessed at each visit: uncorrected distance visual acuity (UDVA), manifest refractive spherical equivalent (MRSE), keratometry values, biomechanical properties, anterior and posterior curvature, and corneal pachymetry. Results. The FS-LASIK Xtra and SMILE Xtra groups both included 24 eyes of 12 patients. At 1, 3, and 12 months after surgery, a UDVA of 20/20 or better was achieved for 91.7%, 91.7%, and 87.5% of individuals, respectively, in the FS-LASIK group and 95.8%, 100%, and 100% in the SMILE group, respectively. For 75% of eyes in the FS-LASIK Xtra group and 100% of eyes in the SMILE Xtra group, the achieved MRSE was within ±1.00D of attempted correction. The LASIK Xtra group had a significantly higher mean MRSE than the SMILE Xtra group at 3 and 12 months after surgery (P=0.006,0.01), and the SMILE Xtra group had significantly higher K1 and K2 values than the FS-LASIK group at one month after surgery (P=0.024,0.023). Corneal thickness decreased significantly at one month postoperatively and started to increase over the next 12 months in both groups (P=0.001). The biomechanical properties showed no significant intergroup differences at the 12-month follow-up. Conclusions. FS-LASIK Xtra and SMILE Xtra are safe and effective in the correction of myopia and myopia astigmatism, and both procedures have the same effect on postoperative corneal morphology and biomechanics.